2009
DOI: 10.1007/s11064-009-9916-9
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Inhibition of Hippocampal and Striatal Adenylyl Cyclase is Mainly Due to the M4 Receptor

Abstract: The five muscarinic acetylcholine receptors (M(1)-M(5)) are differentially expressed in the brain. M(2) and M(4) are coupled to inhibition of stimulated adenylyl cyclase, while M(1), M(3) and M(5) are mainly coupled to the phosphoinositide pathway. We studied the muscarinic receptor regulation of adenylyl cyclase activity in the rat hippocampus, compared to the striatum and amygdala. Basal and forskolin-stimulated adenylyl cyclase activity was higher in the striatum but the muscarinic inhibition was much lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…The M4R is the most abundant striatal muscarinic receptor and it is preferentially expressed in dSPNs where it is clustered near axospinous glutamatergic synapses (Bernard et al, 1992; Hersch et al, 1994). Giant cholinergic interneurons (ChIs) have dense terminal fields that overlap those of DA neurons, allowing M4R suppression of D1R signaling through AC (Jeon et al, 2010; Sánchez et al, 2009). Nevertheless, the role of M4Rs in regulating synaptic plasticity in dSPNs has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The M4R is the most abundant striatal muscarinic receptor and it is preferentially expressed in dSPNs where it is clustered near axospinous glutamatergic synapses (Bernard et al, 1992; Hersch et al, 1994). Giant cholinergic interneurons (ChIs) have dense terminal fields that overlap those of DA neurons, allowing M4R suppression of D1R signaling through AC (Jeon et al, 2010; Sánchez et al, 2009). Nevertheless, the role of M4Rs in regulating synaptic plasticity in dSPNs has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…M2, the other muscarinic receptor negatively coupled to cAMP production, is expressed in cholinergic interneurons (Hersch et al, 1994;Zhao et al, 2016). In the striatum, the negative coupling of M4 to cAMP has already been reported by biochemical measurements on striatal brain slices, whereas M1 receptors, coupled by Gɑq/11, were shown to trigger a modest increase in cAMP (Sánchez-Lemus & Arias-Montaño, 2006;Sánchez et al, 2009). Furthermore, muscarinic stimulation reduced D1-induced cAMP production, an effect that was shown to selectively require M4 receptors in D1 MSNS (Jeon et al, 2010).…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, Shen et al reported that the M 4 mAChR PAM VU10010 blocks aberrant long-term potentiation in direct-pathway spiny projection neurons in an L-3,4-dihydroxyphenylalanine (L-DOPA)-induced dyskinesia (LID) mice model. 43) Because giant cholinergic interneurons have dense terminal fields that overlap those of dopaminergic neurons, they promote M 4 mAChR suppression of dopamine D 1 receptor signaling through adenylyl cyclase, 44,45) leading to the modulation of motor functions. Actually, acute treatment with two other M 4 mAChR PAM, VU0467154 or VU0476406, was found to attenuate LID behaviors in mice and rhesus monkeys.…”
Section: Current Topicsmentioning
confidence: 99%